Health Status of Ageing People A Case Study of Bisharanti Old Aged Home, Mulghat, Dhankuta - Poudel, Tanka Mani (Dristikon: A Multidisciplinary Journal, 2022)
Health is a prime concern for the elderly people who reside in old age homes. Against this backdrop, this research has explored the condition of old aged people regarding their social and health-related issues in an old aged home. The research was carried out among the old-aged people residing at Bishranti Old Aged Home. Among the 40 participants of Bishranti Old Aged Home, 21 participants were selected purposively including 12 females and 9 males. The study concluded that the societal condition including racial, religious, familial and social-economic components were the prime reasons behind their residence in Bishranti Old Aged Home. Due to poor health of the ageing people living in the old aged home, they have been suffered from various physical, mental and social problems. More specifically, the research also indicated that the majority of the participants were victim of hypertension and severe joint pain. Moreover, many of the participants were the victims of diabetes, gastritis, depression, asthma, heart-diseases, chest pain, eye and ear problems etc.